Institutional Quality, Income, and FDI: Unravelling Their Impact on Environmental Degradation in Developing Economies - Imam, Muhammad Asim; Wan Ngah, Wan Azman Saini; Ibrahim, Saifuzzaman; W. Mohamad, Wan Norhidayah (HRMARS, 2024)
This study investigates the role of institutional quality in shaping the relationship between income, FDI, and environmental degradation in developing economies, using a balanced panel dataset of 87 countries from 2000 to 2019. Adopting the Generalized Method of Moments (GMM) estimator, the study explores the Environmental Kuznets Curve (EKC) hypothesis. It examines how institutional factors, such as government effectiveness and the rule of law, influence environmental outcomes. The findings confirm the EKC hypothesis, demonstrating that income initially increases CO2 emissions but eventually leads to reductions as income rises. Institutional quality plays a critical role in mitigating environmental degradation, with stronger governance structures significantly reducing emissions by promoting the enforcement of environmental regulations and facilitating the adoption of clean technologies. The results also reveal that FDI contributes to environmental degradation in countries with weak institutions but can mitigate emissions when supported by effective governance. Furthermore, energy consumption, particularly from non-renewable sources, exacerbates pollution, underscoring the need to transition to renewable energy. The study highlights the importance of institutional reforms, cleaner energy investment, and environmentally responsible FDI in achieving sustainable development in developing countries. The findings provide valuable insights for policymakers balancing income with environmental sustainability.